On Optimality of SAFER-256 Diffusion - Kyuregyan, Knarik M. (Mathematical Problems of Computer Science, 2021)
In this paper it is shown that the new block cipher SAFER-256 provides an optimal diffusion in the sense that the cipher is resistant against differential cryptanalysis attack after minimum possible number of rounds.